2021
DOI: 10.1155/2021/6615584
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Sparsity Adaptive Matching Pursuit Algorithm and Its Application in Shock Wave Testing

Abstract: In the compressed sensing (CS) reconstruction algorithms, the problems of overestimation and large redundancy of candidate atoms will affect the reconstruction accuracy and probability of the algorithm when using Sparsity Adaptive Matching Pursuit (SAMP) algorithm. In this paper, we propose an improved SAMP algorithm based on a double threshold, candidate set reduction, and adaptive backtracking methods. The algorithm uses the double threshold variable step-size method to improve the accuracy of sparsity judgm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In addition, he used an adaptive feedback controller to output the force that determines the amplitude and phase to drive the actuator on the axis in order to reduce the vibration of the box. And the results showed that the vibration decay at the base frequency was about 20-28 dB [5]. Wang, R. et al proposed a new control scheme, in which three magnetostrictive actuators are applied directly on the gear body and the actuator generates a circumferential force to suppress the torsional vibration according to the corresponding control strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, he used an adaptive feedback controller to output the force that determines the amplitude and phase to drive the actuator on the axis in order to reduce the vibration of the box. And the results showed that the vibration decay at the base frequency was about 20-28 dB [5]. Wang, R. et al proposed a new control scheme, in which three magnetostrictive actuators are applied directly on the gear body and the actuator generates a circumferential force to suppress the torsional vibration according to the corresponding control strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the CS reconstruction phase has the same mathematical model as KSVD in the sparse coding phase, many reconstruction algorithms based on adaptive sparse strategies [22,24] are also derived, which can all be applied to the improvement of KSVD dictionary training methods. We summarize the advantages and disadvantages of related works and propose an ASE-KSVD algorithm that combines the estimation method of sparsity in greedy iteration [25][26][27]. e aim is to improve the dictionary training efficiency and reduce the sparsity error while maintaining a lower sparsity.…”
Section: Introductionmentioning
confidence: 99%